APLIKASI MOBILE LEARNING BERBASIS ANDROID UNTUK BELAJAR HURUF HIJAIYAH - fadhilla, aulia; SUheri; Khaliq, Abdul (CV. Hawari, 2021)
Mobile learning is a learning process that utilizes technological developments through electronic devices in the form of smartphones or mobile phones. Currently learning hijaiyah is still widely done by meeting directly with the teaching staff, through Iqra or other print media. With this is considered less effective and ineffective and causes boredom for children. Therefore, an efficient, effective and interactive hijaiyah letter learning medium is needed that is able to increase children's minant power to learn anywhere and anytime. The application will be designed with a system design tool that is UML (Unified Modeling language) that is easy to describe so that it can help in the compounding of the system. The application will be implemented on android-based mobile devices.